Cyber Crime, Victimization against Women in India and It’s Preventive Measures: Understanding and Addressing Cyber Crimes against Women in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Utilization of the Internet keeps on impacting both decidedly and negatively, the social, financial, social, and political parts of each society. Most women who approach Internet don't know about the threats ailing in the Internet. Violence against women is an infringement of human rights and not another marvel. It is continually requiring it shapes investment to time in Indian history. With the progression of time, numerous feminists battled against women violence and for their strengthening in the society, yet there is no closure of her powerless life and her misuse. Because of the data innovation which acquired an extraordinary upheaval the correspondence space for making world a 'Global Village' and giving equivalent acknowledgment of rights to women. Innovation of World Wide Web, cell phones and tabs and so on changed women's standard of living, in spite of the fact that, these developments accompanied immense advantages for us, however it too has some negative consequences for our life and made incredible danger which is commonly known as Cyber Crime. For the most part, cyber crimes happen against women who can be effectively misused. Because of absence of confirmations and dread of defamation, recognizing criminal is exceptionally hard. Cyber violence has presented women to cyber defamation, sexual harassment and abuse, pornography, email-misrepresentation and so forth, in this research study we studied about the cyber crimes against women in India, its Victimization and preventive measures to uphold for stopping them.